The Effect of Social Behavior and Akidah Akhlak Instruction on Students' Humanistic Character - Rahman, Taufiqur; Shoimah Hasan, Nuris; Hosaini, Hosaini (Scidac Plus, 2026)
This study aims to analyze the influence of social behavior and Akidah Akhlak instruction on the development of students’ humanistic character at Madrasah Aliyah. The research is grounded in the growing concern that modern education often emphasizes cognitive achievement while paying less attention to moral and social character formation. In Islamic educational institutions, particularly Madrasah Aliyah, the integration of religious values and social interaction is expected to cultivate empathy, tolerance, and moral responsibility among students. Study Design/Methodology/Approach: This research employs a quantitative approach using a survey method. Data were collected from 160 students at Madrasah Aliyah through structured questionnaires measuring social behavior, Akidah Akhlak instruction, and humanistic character. The data were analyzed using multiple linear regression to determine the extent to which social behavior and religious instruction influence the formation of students’ humanistic character. Statistical analysis was conducted to assess the significance and strength of the relationships among the variables.Findings: The results reveal that both social behavior and Akidah Akhlak instruction significantly influence students’ humanistic character. Social behavior demonstrates a strong contribution to the development of empathy, cooperation, and mutual respect among students. Meanwhile, Akidah Akhlak instruction reinforces moral awareness, ethical responsibility, and spiritual values. The regression analysis indicates that the two variables positively and significantly predict the development of students’ humanistic character.Research Limitations/Implications: This study is limited to one Madrasah Aliyah and relies on self-reported data, which may restrict the generalizability of the findings. In addition, limited technological resources in developing educational contexts may influence data collection and analysis processes.Originality/Value: This research contributes to the discourse on character education by highlighting the integrated role of social interaction and Islamic moral instruction in shaping students’ humanistic character. The findings provide practical implications for educators and policymakers in strengthening character-based education within Islamic schools. Future research may expand the scope by involving multiple institutions and incorporating qualitative approaches to gain deeper insights into the processes of character formation